HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA PUTRI TERHADAP TINGKAT KECEMASAN DENGAN KEJADIAN DISMENOREA DI SMA SWASTA BUDI AGUNG MEDAN - Mulidan; Dedi, Novia Ananda Putri (Jurnal Kesehatan, 2024)
Dysmenorrhea is lower abdominal pain which sometimes extends to the waist and lower back, occurring 2 or 3 years after menarche or the first menstruation. In Indonesia, the incidence of primary dysmenorrhea is around 54.89%, while the rest are sufferers with secondary dysmenorrhea. This study aims to find out the relationship between knowledge and attitudes with levels of anxiety about the incidence of dysmenorrhea at Budi Agung Medan Private High School in 2022. This type of research is an analytic survey with a correlation study time approach (cross-sectional). The population in this study were all young women who had experienced dysmenorrhea at Budi Agung Medan Private High School as many as 67 people by means of purposive sampling. The data analysis used was univariate and bivariate analysis using the chi-square test. The results showed that out of 67 respondents it was found that 48 respondents (71.6%) had less knowledge, and 19 respondents (28.4%) had good knowledge. Then from the results of the attitude it is known that those who have less attitude are 48 respondents (71.6%), and the good ones are 19 respondents (28.4%). While the level of anxiety is less about dysmenorrhea in young women as many as 40 respondents (59.7%). The level of good anxiety about dysmenorrhea in young women was 27 respondents (40.3%). The  results of the Chi-square statistical test using the SPSS application obtained a p-value = 0.03, which means a p-value <0.05. The conclusion is that there is a significant relationship between the knowledge and attitudes of young women and the level of anxiety about dysmenorrhea at Budi Agung Medan Private High School.